Study On Haemato - Biochemical Profile Of Madgyal Sheep From Maharashtra In India - Parekar, S.S.; Patodkar, V.R.; Patil , Mayura R.; Bhong, C.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The hamatological and serum biochemical values of madgyal sheep were within the reference range of sheep with the exception of TEC values, which were slightly lower than the reference values. TEC, Hb, PCV, total protein and albumin values in male sheep (7.87 ± 0.15, 10.18 ± 0.19, 33.13 ± 0.49, 7.75 ± 0.12 and 3.65 ± 0.06 respectively) were significantly (P
Keywords: Madgyal sheep; haematology; serum biochemical profile